Doktrin Kristus (Kristologi) - Triani Cahyaningsi; Helena Regalia Ujabi; Sarmauli Sarmauli (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The doctrine of Christ or Christology is the core part of Christian teaching that studies the person and work of Jesus Christ. As the core of the Christian faith, Christology discusses who Jesus is, both in His divinity as the Son of God and in His humanity who was present in the world to atone for human sins. A correct understanding of Christology is very important because it influences how Christians understand salvation, the sacrifice on the cross, and the resurrection of Jesus from the dead. However, in an increasingly modern and pluralistic era, this doctrine often faces quite complex challenges.